A autonomia de bebês na creche - PINTO, Thayse Wanzeler (2020)
This article seeks to deepen the studies and reflections on the contributions of the Pikler Approach to the development of pedagogical practices that favor the autonomous development of the young children. This approach is based on the understanding of the baby as an active social subject, and on its role in spaces with the materials and collective environments, in interactions with others and adults. The text aims to know how to work the autonomy of the baby in day care, the light of Emmi Pikler and present the principles that encompass the approach. To do so, I used works by Emmi Pikler, his collaborators Judith Falk and Anna Tardos, and by scholars of Pikler, such as Paulo Fochi and Agnes Szanto-Feder. This study is of bibliographic character. Initially I made a broad leap that discuss the development of autonomy in infants, from this study and understanding the approach was chosen to deepen only the ideas of Emmi Pikler, about the principles of the approach in order to understand how to build the autonomy in babies. The research concluded that the teacher is a great partner in this process of development of the baby, and that he is a competent subject that needs to experience freedom of movement, it is essential that the collective environment is organized for babies to have safety in their movements, and moments of bodily care are important to them in this stage of autonomy development.